Konzentration statt Verzettelung: die deutsche Arbeitsmarktpolitik am Scheideweg - Hilmar Schneider; Werner Eichhorst; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The German labor market reforms seem to be on the right track. However, they need to be adjusted especially on the organizational side to make them more effective. The labor market instruments can be concentrated on temporary company wage subsidies, training measures and financial incentives for business start-ups. It is essential to increase incentives, intensify competitive structures and to ensure clear-cut responsibilities.
Keywords: J65; J68; J69; 330; labor market policy; evaluation of active labor market policies; public policy; unemployment insurance